Methodological proposal of identification of the high, medium and low course of the Cocó river hydrographic basin, Ceará, Brazil - França, Rosilene de Melo (Geosaberes, 2019)
The hydrographic basin is an important water system responsible for providing water to a society. The technical-scientific effort to understand the hydrological processes is evidenced through the various studies focused on compartmentalization of the basin in three sectors: high, medium and low course. Despite the existence of works on this subject, methodologically, it still lacks forms of delimitation applied to the existing theory. This research intends to compartmentalize the catchment area of ​​the Cocó river. The study area covers the Cocó river basin, which is located in the municipality of Fortaleza and in some municipalities of the Metropolitan Region (Pacatuba, Maracanaú, Maranguape, Itaitinga, Aquiraz and Eusébio), territorially comprising an area of ​​approximately 517 km². In order to carry out this research, some methodological procedures were necessary, such as: bibliographical survey, field visits and use of geoprocessing software. With this, it was possible to perceive that drainage in the high-rise area exerts erosive power on the relief; While in the medium course they are presented as transport agents and finally, in the low course are characterized by the deposition of sediments in its margins.